The Effectiveness of Group Guidance to Improve Students' Social Interaction Skills - Inayatul Khafidhoh (Al Hikmah: Journal of Education, 2021)
The purpose of this article is to find out the effectiveness of group guidance to improve student social interaction. This research belongs to the type of Action research. This study uses two cycles, with stages of planning, activities, observation and reflection. The sample in this study amounted to 10 students. The results of this study are 1) students' social interaction skills are in the low category 2) the implementation of group guidance to improve students' social interaction skills is carried out through two cycles and four meetings, 3) students' social interaction skills level increases after receiving group guidance services. Based on the results of the T test, it is found that Tcalculate 0 ≤ Ttable 8 or means that Ha is accepted and Ho is rejected. The results showed that students' social interaction skills improved after receiving group tutoring services. In other words, social interaction skills can be improved through group tutoring services.Group guidance; social interaction skills, Junior High School Students